ANALISIS PENGOLAHAN DATA SEISMIK LAPANGAN “R” DENGAN METODE CRS (COMMON REFLECTION SURFACE) STACK PADA DATA CROSS SECTION MARINE 2D - Rezyta Handani; Udi Harmoko; Istiqomah Ari Kusuma (Youngster Physics Journal, 2015)
ABSTRACTIn complex geological data processing, conventional method has not been able to produce good imaging. The result of conventional method processing can be supported by Common Reflection Surface Method (CRS) stacking. This method is believed to have better mathematical operation compared to conventional method, especially in Normal Move Out (NMO) correction. CRS stack method using correct operator stacking for recorded reflector in pre-stack data is proven better than conventional method. Operator CRS stacking consists of 3 kinematic wavefield attributes namely α, RNIP and RN. CRS stacking process to acquire good CRS section involved angle, aperture, and dip test. The selected parameter was then released as CRS supergather which then was used as the input of PSTM process. The best CRS operator was obtained using the parameters as follows:  apperture 500 – 2000m and angle 45˚. This result was able to increase the continuity and the reflector accuracy. Nevertheless, CRS stack also caused spectrum reduction in high frequency but it was able to be overcomed using Whitening. CRS supergather shows better result than conventional supergather using PSTM process. During the research, CRS analysis in the cross section of two tracks as the development of CRS application was also performed, where the sections resulted from CRS Stack did not influence the cross section of those two tracts.